The effect of IL10 gene polymorphism on obesity parameters in highly physically active young men - Maculewicz, Ewelina; Mastalerz, Andrzej; Antkowiak, Bożena; Antkowiak, Oktawiusz; Garbacz, Aleksandra; Szarska, Ewa; Rusin, Paweł; Cywińska, Anna; Białek, Agnieszka; Cięszczyk, Paweł (Biology of Sport, 2022)
The main aim of this study was to investigate the association between 5 polymorphisms of the interleukin 10 (IL10) gene and body composition parameters in physically active young men. A cohort of 131 young men was enrolled and the following IL10 single-nucleotide polymorphisms (SNPs) were analysed: rs1518111, rs1878672, rs3024496, rs3024498 and rs3024505. The subjects were divided into groups depending on obesity parameters: body mass index (BMI) and percentage of body fat tissue (fat %). Statistical analysis was conducted for alleles, genotypes and haplotypes, and an association between SNPs and body composition parameters was analysed using four genetic models: dominant, recessive, codominant and overdominant mode of inheritance (MOI). The only statistically significant result in polymorphisms was found for rs3024505 in the over-dominant model with BMI (p = 0.04) and with fat % (p = 0.02). The haplo.score function showed an association between BMI and CCGTA (respectively) haplotype in the additive model (score = -2.00, p = 0.04) and in the dominant model (score = -2.30, p = 0.02). The obtained results indicate a statistically significant contribution of selected IL10 polymorphisms in the regulation of body weight in physically active individuals.